2018
DOI: 10.1038/s41598-018-23592-z
|View full text |Cite
|
Sign up to set email alerts
|

Blocking distinct interactions between Glioblastoma cells and their tissue microenvironment: A novel multi-targeted therapeutic approach

Abstract: Due to the highly invasive nature of Glioblastoma (GB), complete surgical resection is not feasible, while motile tumour cells are often associated with several specific brain structures that enhance treatment-resistance. Here, we investigate the therapeutic potential of Disulfiram and Carbenoxolone, that inhibit two distinct interactions between GB and the brain tissue microenvironment: stress-induced cell-matrix adhesion and gap junction mediated cell-cell communication, respectively. Increase in cell number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…ROS-dependent therapies that target mitochondria, range from photodynamic therapy, to compounds such as retinoic acid and arsenic trioxide that directly target sub-structures (142). It has been recently shown that ROS can modulate microtubule dynamics in the course of the EB1 phosphorylation process (143).…”
Section: Therapy Highlights For Targeting Mitochondria In Apoptosis Imentioning
confidence: 99%
“…ROS-dependent therapies that target mitochondria, range from photodynamic therapy, to compounds such as retinoic acid and arsenic trioxide that directly target sub-structures (142). It has been recently shown that ROS can modulate microtubule dynamics in the course of the EB1 phosphorylation process (143).…”
Section: Therapy Highlights For Targeting Mitochondria In Apoptosis Imentioning
confidence: 99%
“…(iv) CSPG-induced cell-ECM bonding was mediated by its receptor LAR and LAR-CSGAG complex [ 42 ]. Integrins usually mediate the cell-matrix interactions by tethering the cell to its surrounding ECM and activating intracellular signalling cascades [ 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…A glioma interacts with its microenvironment such as stromal cells (astrocytes, neurons, microglia, macrophages), ECM, vessels, and chemokines/cytokines by direct and indirect contacts in the tumor-stroma network [ 42 , 43 , 47 , 48 ]. M1 and M2 types of microglia were shown to promote glioma cell invasion by exchanging signaling molecules such as CSF-1, EGF and TGF- β [ 49 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…Current available studies on pharmacological gap junction inhibition in glioblastoma are mainly based on the use of the glycyrrhetinic acid-derivative carbenoxolone as a potent gap junction blocker [22,23,24,25,26,27]. However, carbenoxolone has been shown not to reach therapeutically relevant concentrations for gap junction inhibition in the brain interstitium after systemic administration [28].…”
Section: Discussionmentioning
confidence: 99%